WhatsApp as a Tool for Participation on Spanish Radio: A Preliminary Study of the Program Las Mañanas on RNE (2018)
This study was conducted in an environment of widespread use of social media and mobile applications in the mass media. The general goal of the study was to analyze the use of WhatsApp in cybermedia, specifically in radio. A case study was proposed to examine the use of WhatsApp on the program Las mañanas de RNE, broadcast by Spanish National Radio. It was found that the public was very accepting of the program’s initiative to solicit WhatsApp voice messages, beginning in November 2015. The case study used audio files of a direct broadcast that included specific times for audience participation. The use of WhatsApp was accepted by the audience, in addition to the use of the conventional telephone, as a tool well-suited to listener participation in radio programming. Finally, the study highlights the importance of interactive, participatory spaces in broadcasts through the creation of synergies with new forms of online participation. © 2018 Broadcast Education Association.